2020
DOI: 10.1007/s10854-020-04242-5
|View full text |Cite
|
Sign up to set email alerts
|

SnO2 nanoparticles synthesized with Citrus aurantifolia and their performance in photocatalysis

Abstract: This research presents an alternative tin oxide (SnO 2) nanoparticles synthesis method using different concentrations of Citrus aurantifolia peel extract as reducing agent. We report the chemical identification protocol for polyphenols in the peels via FTIR, the characterization of the SnO 2 nanoparticles by FTIR, XRD, HRTEM, and UV-vis. The SnO 2 nanoparticles presented the Sn-O-Sn bond at 640 cm −1 and crystal growth with a clearly tetragonal structure. Depending on the amount of extract used, hemispherical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…Due to the large size of the nanoparticles, the bandgap decreased. In addition, the synthesized materials exhibit values that are similar to those of bulk SnO 2 (3.6 eV) [37,40] which suggests that they can be used in photocatalytic applications [37] …”
Section: Resultsmentioning
confidence: 68%
“…Due to the large size of the nanoparticles, the bandgap decreased. In addition, the synthesized materials exhibit values that are similar to those of bulk SnO 2 (3.6 eV) [37,40] which suggests that they can be used in photocatalytic applications [37] …”
Section: Resultsmentioning
confidence: 68%
“…Other studies have found similar outcomes with different dopants in the past. , As the crystallite size reduced, the surface area of the photocatalyst becomes large, improving the adsorption of the reactant and absorption of light over the photocatalyst. Consequently, PCA was increased by doping CS and Mg in SnO 2 because the crystallite size was reduced, as elaborated in Table . The CA of SnO 2 was also increased as the crystallite size decreased, attributed to the large surface area of the catalyst .…”
Section: Resultsmentioning
confidence: 97%
“…31 The CA of SnO 2 was also increased as the crystallite size decreased, attributed to the large surface area of the catalyst. 31 Moreover, SAED analysis of primeval and doped samples revealed 32 The transmission bands at 3356 and 1633 cm −1 can be allocated to the O−H vibration. 33 Upon doping of CS, bands move toward the lower wavenumber, representing the presence of the −OH or NH 2 functional group in CS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations